PENERJEMAHAN KALIMAT YANG MENGAKOMODASI TINDAK TUTUR MENGELUH DALAM FILM SEX AND THE CITY SEASON 6 - Fajar Nur Pratiwi; Mangatur Nababan; Riyadi Santosa (Universitas Sebelas Maret, 2017)
ABSTRACT (English)This study focused on the translation of sentences that represent speech complain in subtitle entitled Sex and the City Season 6. The purpose of this study are: (a) describe the type of strategies complain used in novel Sex and the City Season (b) finding techniques translation speech sentences containing tutr acts complained of (c) describes the impact of the type of utterances of speech acts complained of the quality of the translation. The results of this study are: (a) Strategy speech acts complained realized in 7 types, namely strategy hints, annoyance, ill consequences, indirect accusation, direct accusation, modified blame, explicit blame of the Accused's action, explicit blame of the Accused as a person , (B) translation techniques used in translating the speech acts complained of in the form of a single translation techniques and couplets. However, the translation of the speech act complained of has been very good, with the final results third weighting translation quality (accuracy, acceptability, legibility), amounting to 2.92. Keywords: speech complain, complain strategy, speech acts, translation, technical translation, translation quality